(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this study is to shed more light on the effects and significance of talent management as a recent system in the context of achieving digital transformation and its multiple activities, particularly in the new era. It also comes not only to survey the motivations for approving such a concept in organizations and companies, as well as the impact on their employees, but also to identify the most important talent management strategies and how to deal with its considered digital transformation of future India for its direct impact on performance level, as well as to identify the best ways to invest in talent management because of the effects on increasing the economy in the organization by retaining employees. Employees, particularly skilled ones, contribute to digital transformation because they innovate in their fields and have the ability to make the appropriate decisions to achieve goals.